2018
DOI: 10.1080/02699931.2018.1433128
|View full text |Cite
|
Sign up to set email alerts
|

Empathic accuracy: age differences from adolescence into middle adulthood

Abstract: This study investigated age differences in empathic accuracy, the ability to correctly perceive others' emotions, in a sample of 151 boys and men from three age groups: adolescents (M = 16 years, SD = 1.04), young adults (M = 29 years, SD = 2.78), and middle-aged adults (M = 50 years, SD = 3.07). All participants viewed nine newly developed film clips, each depicting a boy or a man reliving one of three emotions (anger, sadness, or happiness), while talking about an autobiographical memory. Adolescents and mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
2
21
1
3
Order By: Relevance
“…By employing ecologically valid tasks tailored to a context central to most adults, namely the work context, and integrating middle-aged adults (i.e., relatively old workers), we corroborated past work. Our findings suggest that recognizing others' emotions accurately may already decrease in middle adulthood (similar to Isaacowitz et al, 2007;Kunzmann et al, 2018), while our findings match studies that largely omit middle age by showing that older workers shared other people's emotions equally well as younger ones and even reported higher sympathy (Bailey et al, 2018;. Thus, age deficits in empathic accuracy are already evident at an age that often is considered as middle age and conceptualizations of midlife as a period of prime performance may be in need of qualification.…”
Section: Multidirectional Age Differences In Empathysupporting
confidence: 87%
“…By employing ecologically valid tasks tailored to a context central to most adults, namely the work context, and integrating middle-aged adults (i.e., relatively old workers), we corroborated past work. Our findings suggest that recognizing others' emotions accurately may already decrease in middle adulthood (similar to Isaacowitz et al, 2007;Kunzmann et al, 2018), while our findings match studies that largely omit middle age by showing that older workers shared other people's emotions equally well as younger ones and even reported higher sympathy (Bailey et al, 2018;. Thus, age deficits in empathic accuracy are already evident at an age that often is considered as middle age and conceptualizations of midlife as a period of prime performance may be in need of qualification.…”
Section: Multidirectional Age Differences In Empathysupporting
confidence: 87%
“…In contrast with past studies that show a female advantage in empathy across the lifespan (Kunzmann, Wieck, & Dietzel, 2018), the present results did not reveal any gender differences in children's empathy for companion animals. This finding could have been due to a variety of reasons.…”
Section: Gender Differencescontrasting
confidence: 99%
“…Previously, Greimel et al [24] found that male adolescents and young male adults showed no differences in a task requiring identification of other's emotions. Contrastingly, Kunzmann et al [25] found that the ability to accurately recognize another's emotion was significantly worse in a male adolescent group compared to a male adult group. The ability to accurately identify another's emotion is part of emotion recognition [26], which is a component of cognitive empathy [4,8,19].…”
Section: Discussionmentioning
confidence: 88%